a)\(\left|2x+3\right|=x+2\)
\(\Leftrightarrow\left(\left|2x+3\right|\right)^2=\left(x+2\right)^2\)
\(\Leftrightarrow4x^2+12x+9=x^2+4x+4\)
\(\Leftrightarrow3x^2+8x+5=0\)
\(\Leftrightarrow3x^2+3x+5x+5=0\)
\(\Leftrightarrow3x\left(x+1\right)+5\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(3x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+1=0\\3x+5=0\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=-\dfrac{5}{3}\end{matrix}\right.\)
b)\(x^2-9x+8=0\)
\(\Leftrightarrow x^2-8x-x+8=0\)
\(\Leftrightarrow x\left(x-8\right)-\left(x-8\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-8\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1=0\\x-8=0\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=8\end{matrix}\right.\)
c)\(x^2-2\left(x-2\right)=4\)
\(\Leftrightarrow\left(x^2-4\right)-2\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x+2\right)-2\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x+2-2\right)=0\)
\(\Leftrightarrow x\left(x-2\right)=0\)\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\end{matrix}\right.\)
b/ \(x^2-9x+8=0\)
Ta có: a = 1 ; b = -9 ; c = 8
\(\Delta=b^2-4ac=\left(-9\right)^2-4.1.8=49\)
\(\Rightarrow\sqrt{\Delta}=7\)
Pt có 2 nghiệm:
\(x_1=\dfrac{-b+\sqrt{\Delta}}{2a}=\dfrac{9+7}{2.1}=8\)
\(x_2=\dfrac{-b-\sqrt{\Delta}}{2a}=\dfrac{9-7}{2.1}=1\)
Vậy.......................................